Znęcanie nad zwierzęciem w doktrynie prawa karnego i w orzecznictwie sądowym — kilka uwag tytułem wstępu do rozważań o prawnej ochronie zwierząt - Helios, Joanna; Jedlecka, Wioletta (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Legal protection of animals in Poland is becoming more and more important, which is probably contributed to international regulations and, which cannot be marginalized, the EU. This text is an introduction to the legal protection of animals. Two groups of problems are separated: first — an analysis of cruelty to animals, and secondly — the problem of mistreatment of animals in court decisions.
Keywords: ochrona prawna zwierząt; Polska; orzecznictwo sądowe; okrucieństwo wobec zwierząt; złe traktowanie zwierząt